CyberAll: A Personal Store of Everything - Bell, Gordon (2000)
CyberAll is a project to archive all my personal and professional information content including that which has been computer generated (since the mid 70s), scanned and recognized, and recorded on VHS tapes. The archive includes books, correspondence (i.e. letters, memos, and email), transactions, papers, photos and photo albums, and video taped lectures. In 2000, only 10 gigabytes, costing 100 incrementally, are required, and the accumulation rate is projected to be 1-2 gigabytes per year. Encoding, indexing, and data-management costs swamp storage costs – by 1000:1 or more. The clear challenge is to automate the capture, search, and retrieval so that it comes close to the storage cost. It is inconceivable to think of manually managing or purging this electronic file since the storage costs are only 100. Indeed, copies are stored in 2 or 3 locations for redundancy.